Rifampin Based Therapy for Patients With Staphylococcus aureus Native Vertebral Osteomyelitis: A Systematic Review and Meta-analysis - El Zein, Said; Berbari, Elie F; Passerini, Matteo; Petri, Francesco; Maamari, Julian; Murad, M Hassan; Sendi, Parham; Tande, Aaron J (Clinical infectious diseases, 2024)
Native vertebral osteomyelitis (NVO) caused by Staphylococcus aureus is associated with high risk of treatment failure and increased morbidity. The role of rifampin-based therapy for the treatment of this condition is controversial. The goal of this systematic review and meta-analysis is to explore the efficacy and safety of rifampin-based therapy for the treatment of S. aureus NVO. We searched Cochrane, Embase, Medline, Scopus, and Web of Science databases for studies published up to May 2023, focusing on adults with NVO treated with or without rifampin-containing regimens. A random-effects model meta-analysis estimated relative risks and risk difference with 95% confidence intervals (CI). Thirteen studies (2 randomized controlled trials and 11 comparative cohort studies), comprising 244 patients with S. aureus NVO who received rifampin and 435 who did not, were analyzed. Meta-analysis showed that rifampin-based regimens were associated with lower risk of clinical failure (risk difference, -14%; 95% CI, -19% to -8%; P < .001; I2 = 0%; relative risk, 0.58; 95% CI, .37-.92, P = .02, I2 = 21%). Only 1 study reported on adverse events. All studies had a high or uncertain risk of bias, and the certainty of evidence was rated as very low. Adjunctive rifampin therapy might be associated with lower risk of S. aureus NVO treatment failure; however, the low certainty of evidence precludes drawing definitive conclusions that would alter clinical practice. A randomized trial is necessary to corroborate these findings.